Site Plan Analysis Based on Measured and Unmeasured Criteria for Housing Development According to Investor Assessment - Aryani, Ni Putu; Wahyuadi, Hendra; Kusumowidagdo, Astrid; Fayola, Karen; Widodo, Stephanie Kaori (Tekstur (Jurnal Arsitektur), 2023)
The high rate of urbanization has encouraged housing development to meet housing needs, especially in border areas. This research was conducted to obtain investment feasibility data by professionals/investors. Three Site Plan designs that have different lot sizes and house types were analysed simultaneously. Quantitative and qualitative methods were used to analyse the measurable criteria and unmeasured criteria. The results of both were assessed by investors using rational-intuitive decision models. This study finds, the analysis of measurable criteria produces Site Plan A having 60 lots with the lowest production costs and selling prices. Meanwhile, Site Plan B and Site Plan C planned 37 and 35 lots with higher production costs and selling prices. Therefore, the financial feasibility simulation generated a significant difference. The results of the analysis of unmeasured criteria indicated that the different category values of each Site Plan dominated each other. The rational-intuitive model divided the percentage based on profit, which was 75% measurable and 25% unmeasurable. The calculation results stated that Site Plan A was more feasible to implement financially and fulfilled the planning as part of an urban area. In conclusion, the results of measured and unmeasured analyses had significant differences. However, by evaluating rational-intuitive decision models performed by professionals, decisions that meet both types of analysis could be produced. Therefore, the calculation of financial feasibility is not the only tool to determine the feasibility of a project. The ability of an investor is also a determining factor in deciding the feasibility of an investment.